Results of research of higher nervous activity problems by Ukrainian scientists in Prielbrussie - Білошицький, П.В.; Ключко, О.М.; Онопчук, Ю.М.; Колчинська, А.З. (Proceedings of National Aviation University (archive), 2022)
Some results of central nervous system investigation and hypoxia influence in mountain conditions are given as well as methods for professional selection developed on this base. Mathematic model for the estimation of brain hypoxia due to glioma development is suggested.